EVALUASI ALINEMEN VERTIKAL RUAS JALAN DESA TIMBONG KECAMATAN BANGGAI TENGAH KABUPATEN BANGGAI LAUT - Indrianiti, Susanna (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2022)
This research was conducted in the village of Timbong, Central Banggai District, Banggai Laut Regency, Central Sulawesi. The purpose of this research is to evaluate the suitability of vertical alignment planning based on current traffic conditions using Bina Marga guidelines No.038/TBM?1997. Based on the evaluation results with vehicle data, the ideal lane and shoulder width according to the determination of the roadway and shoulder widths is 6.0m and 1.0m. Meanwhile, the results of the evaluation of the design speed, based on the equation that has been determined for the stopping sight distance with the design speed of 28, 83m to 35.61m. and by looking at the results of the actual measurement of the width of the lane in the vertical alignment it fits even beyond the predetermined ideal width of 6.40m but does not yet have a shoulder, a slope value of 10% is not in accordance with the rules, namely a maximum of 9% but is still categorized as safe. Therefore, there must be additional traffic signs on the Timbong village road, Central Banggai District, Banggai Laut Regency because of the 10% slope, this is so that road users are more careful to anticipate accidents even though the road is still categorized as safe.